Reformulasi Konsep Pengampuan Melalui Penguatan Pengawasan oleh Pengampu Pengawas - Fouziah, Resti; Hadi, Syofyan (CV. Era Digital Nusantara, 2025)
The concept of guardianship in the Civil Code (KUH Perdata) has so far contained a discriminatory approach towards people with mental and/or intellectual disabilities. This is reflected in the use of terms such as